DEVELOPMENT OF ENGLISH TEACHING MATERIALS WITH POSTER PRESENTATION ASSISTED VLOG - Rasmita Rasmita; Shally Amna (AL-ISHLAH: Jurnal Pendidikan, 2020)
The purpose of this research is to produce English language teaching materials 1 through the implementation of poster presentation assisted vlog strategies for improving language skills and student learning outcomes at private Universities in Padang. This research uses research and development (RD) methods. The stages of development in this study using the development procedures of the Puslitjaknov team include; (1) needs analysis, (2) initial product development, (3) expert validation and revision, (4) small-scale field trials, (5) large-scale field trials. Data collection methods in this study are the observation sheets, questionnaires, expert validation sheets and evaluation (tests). The results of this development research are effective and applicable English 1 teaching materials used for non-English major students.